Land tenure security and internal migration in Tanzania - Tseday Jemaneh Mekasha; Wilhelm Ngasamiaku; Remidius D. Ruhinduka; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
In this paper we study the impact of tenure security on rural to urban migration of household members over the age of 15. Using three waves of the Tanzanian National Panel Survey (NPS) data, we show that tenure security is associated with lower probability of migration in rural Tanzania. This result is consistent with the idea that better property rights over agricultural land in rural Tanzania, by easing the fear of expropriation of land holdings, can induce households to retain more of their members. The result is found to be robust to different specifications and estimation techniques. Promoting land tenure security is a key policy concern in curbing rural - urban migration at early stages of development.
Keywords: O15; Q15; Q18; Q24; 330; migration; Tanzania; tenure security